2015
DOI: 10.18632/oncotarget.5356
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing NRIP1 inhibits growth of breast cancer cells in vitro and in vivo

Abstract: Earlier age at menarche is a major risk factor for breast cancer. Our previous study identified Nrip1 (also known as Rip140) as a candidate gene for delaying female sexual maturation (FSM) and found that knocking out Nrip1 could significantly delay FSM in mice. To investigate the effects of NRIP1 in breast cancer we used human cell lines and tissue arrays along with an in vivo study of DMBA-induced carcinogenesis in Nrip1 knockout mice. Analysis of tissue arrays found that NRIP1 is elevated in tumors compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 24 publications
2
48
1
Order By: Relevance
“…Lapierre et al (17) revealed that expression of RIP140 in colon carcinoma was low, and that overexpression of RIP140 in colon cancer cells promoted the expression of adenomatous polyposis coli, which inhibited the growth and metastasis of colon cancer by inhibiting the Wnt/APC/β-catenin signaling pathway. However, Aziz et al (8) demonstrated that RIP140 was highly expressed in breast cancer tissues, and that inhibition of RIP140 expression in breast cancer cells inhibited growth, proliferation and invasion in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lapierre et al (17) revealed that expression of RIP140 in colon carcinoma was low, and that overexpression of RIP140 in colon cancer cells promoted the expression of adenomatous polyposis coli, which inhibited the growth and metastasis of colon cancer by inhibiting the Wnt/APC/β-catenin signaling pathway. However, Aziz et al (8) demonstrated that RIP140 was highly expressed in breast cancer tissues, and that inhibition of RIP140 expression in breast cancer cells inhibited growth, proliferation and invasion in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…RIP140 also affects tumorigenesis and tumor metastasis via E2F transcription factor and Wnt/adenomatous polyposis coli (APC)/β-catenin signaling pathways (5,7). Aziz et al (8) demonstrated that inhibition of RIP140 inhibited the growth of breast cancer cells in vivo and in vitro. However, to the best of our knowledge, no previous research has investigated the association between the expression of RIP140 in TNBC and the postoperative prognosis of patients with TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Th e changes in these genes expression in cells without IRE1 signaling enzyme function possible contribute in the suppression of glioma cell proliferation and tumor growth, because there are data indicating that the estrogen receptor related factors play an important role in the control of cell proliferation and apoptosis (Cho et al 2010;Lapierre et al 2015;Tiwari et al 2015). It is possible that increased expression of FAM162A, PGRMC2, TRIM16 and SLC39A6 genes as well as decreased expression of ESRRA, and NRIP1 genes (Figure 1) may contribute to the suppression of the proliferation and glioma growth from glioma cells with IRE1 knockdown (Auf et al 2010(Auf et al , 2013Aziz et al 2015;Casaburi et al 2015;Minchenko et al 2015;Zhang et al 2015;Matsushima et al 2016). Th erefore, suppressing of NRIP1, which modulates transcriptional activity of the estrogen receptor, as well as knockdown of a site-specifi c transcription regulator ESRRA/NR3B1 inhibits growth of the cancer cells in vitro and in vivo (Aziz et al 2015;Matsushima et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased expression of FAM162A, PGRMC2, TRIM16 and SLC39A6 genes as well as decreased expression of ESRRA, and NRIP1 genes (Figure 1) may contribute to the suppression of the proliferation and glioma growth from glioma cells with IRE1 knockdown (Auf et al 2010(Auf et al , 2013Aziz et al 2015;Casaburi et al 2015;Minchenko et al 2015;Zhang et al 2015;Matsushima et al 2016). Th erefore, suppressing of NRIP1, which modulates transcriptional activity of the estrogen receptor, as well as knockdown of a site-specifi c transcription regulator ESRRA/NR3B1 inhibits growth of the cancer cells in vitro and in vivo (Aziz et al 2015;Matsushima et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation